Foreign resources and development in India - "Deb, Kalipad" (New Delhi, 1982)
The study tries to put into clear focus, how far the use of foreign re sources are responsible for the mis direction, inefficiencies and corruption in our development efforts. It looks into the resource base of the country and the development aimed at, the balance of socio-economic and poll tical forces, and distortion of plan priorities and the strengthening of foreign powers' grip on the economy for an unending exploitation. The study explores, for the first time, the systemic approach involved in foreign private investment, technical collabo rations and foreign aid for deepening the country's dependence. The con tributions of the bureaucrats, policy makers and the domestic business houses in this process have also been analyzed.
Keywords: Economic assistance India